2013
DOI: 10.1158/0008-5472.can-12-2601
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation by Z-DNA Silencer Function Controls Cancer-Associated ADAM-12 Expression in Breast Cancer: Cross-talk between MeCP2 and NF1 Transcription Factor Family

Abstract: A disintegrin and metalloprotease domain-containing protein 12 (ADAM-12) is upregulated in many human cancers and promotes cancer metastasis. Increased urinary level of ADAM-12 in breast and bladder cancers correlates with disease progression. However, the mechanism of its induction in cancer remains less understood. Previously, we reported a Z-DNA-forming negative regulatory element (NRE) in ADAM-12 that functions as a transcriptional suppressor to maintain a low-level expression of ADAM-12 in most normal cel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 40 publications
1
39
0
Order By: Relevance
“…On the other hand, MeCP2 is the first methyl-cytosine-phosphate-guanine-binding domain protein discovered in its family which acts as a chromatin regulator of transcription and is encoded by the gene mutated in the neurodevelopmental disorder Rett syndrome (LaSalle and Yasui, 2009). MeCP2, usually overexpressed in human carcinomas, promotes the growth and invasiveness of many types of cancer cells, including breast carcinoma cells (Billard et al, 2002;Ray et al, 2013), and may modulate ABCB1/MDR1 expression (El-Osta and Wolffe, 2001). FOXA2, a transcription factor belonging to the forkhead class of DNA-binding proteins, is revealed as an important regulator in promoting pancreatic/hepatic/colorectal cell differentiation and organ development (Gao et al, 2008;Song et al, 2010) and regulating the expression of some (proto-)oncogenes ) and a number of ABC transporters (Bochkis et al, 2008(Bochkis et al, , 2012.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, MeCP2 is the first methyl-cytosine-phosphate-guanine-binding domain protein discovered in its family which acts as a chromatin regulator of transcription and is encoded by the gene mutated in the neurodevelopmental disorder Rett syndrome (LaSalle and Yasui, 2009). MeCP2, usually overexpressed in human carcinomas, promotes the growth and invasiveness of many types of cancer cells, including breast carcinoma cells (Billard et al, 2002;Ray et al, 2013), and may modulate ABCB1/MDR1 expression (El-Osta and Wolffe, 2001). FOXA2, a transcription factor belonging to the forkhead class of DNA-binding proteins, is revealed as an important regulator in promoting pancreatic/hepatic/colorectal cell differentiation and organ development (Gao et al, 2008;Song et al, 2010) and regulating the expression of some (proto-)oncogenes ) and a number of ABC transporters (Bochkis et al, 2008(Bochkis et al, , 2012.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that MeCP2 is abundantly expressed in numerous cancer cells, such as breast cancer (Ray et al, 2013), osteosarcoma (Meng et al, 2015) and melanoma (Sarkar et al, It was originally reported that MeCP2 was associated with transcriptionally repressed genes (Nan et al, 1997) and could interact with another transcriptional repressor Sin3A to recruit HDAC to inhibit transcription of methylated promoters (Nan et al, 1998). Furthermore, MeCP2 was found later to also have a previously uncharacterized function as a splice site regulator (Young et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising, because many cancer-related genes are silenced by epigenetic mechanisms, specifically promoter hypermethylation (Fukushige and Horii 2013). The relation between MeCP2 and breast cancer is well established, where MeCP2 is involved in epigenetic regulation of breast cancer-related genes (Mirza et al 2013;Ray et al 2013;Sapkota et al 2012;Muller et al 2003). Moreover, the expression and potential importance of MeCP2 in prostate cancer were shown previously (Shu et al 2011;Yaqinuddin et al 2008;Bernard et al 2006).…”
Section: Cancermentioning
confidence: 94%